Ultra-Processed Food Consumption and Obesity: A Narrative Review of Their Association and Potential Mechanisms - Jee-Seon Shim (Journal of Obesity & Metabolic Syndrome)
Obesity is a major global health concern, with diet playing a crucial role in its development and treatment. Ultra-processed foods (UPFs) have become prevalent in diets due to changes in the food environment. These foods are energy-dense; high in fat, sugars, or salt; and low in fiber, protein, vitamins, and minerals, raising concerns about their effects on health. In addition to traditional research focused on nutrients, food, and dietary quality, growing evidence has linked UPF consumption to obesity. Therefore, this study provides a comprehensive review of the levels and trends of UPF consumption, current epidemiological evidence on the association between UPF consumption and obesity, and UPFs’ potential role in the etiology of obesity and weight gain. Additionally, this study reviews strategies for reducing UPF consumption and outlines future studies of the link between UPF consumption and obesity.